Physico-hydric conditions of an Alfisol cultivated with soybean under no-tillage and conventional tillage - Ribeiro, Pablo Lacerda; Bamberg, Adilson Luís; Reis, Diony Alves; Oliveira, Ana Cláudia Barneche de (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the effects of no-tillage (NT) and conventional tillage (CT) on the physical and hydric properties of an Albaqualf soil cultivated with soybean, in the lowlands of Southern Brazil. Undisturbed soil samples were collected at the 0.00–0.10, 0.10–0.20, and 0.20–0.40-m soil layers, in order to determine soil physicohydric properties, by monitoring the soil matric potential with sensors, over a cycle of soybean production. Macroporosity values were lower than 0.10 m3 m-3, irrespectively of the soil management system, which restricts the possibility of rainfed soybean cultivation because it affects gas diffusion. In comparison to CT, NT increases microporosity at the 0.00–0.10-m soil layer, which increases soil water content and soil water availability for soybean crop, with positive effects on crop yield.